Amphiphilic Iminosugar Pharmacological Chaperones towards β‐Glucocerebrosidase: Self‐Assembly and Biological Activity. Issue 11 (5th December 2022) - Vanni, Costanza; Cardona, Francesca; Clemente, Francesca; Morrone, Amelia; Raudino, Martina; Ambrosi, Moira; Lo Nostro, Pierandrea; Matassini, Camilla
Abstract: Pharmacological chaperones (PCs) can restore correct enzymatic activity at sub‐inhibitory concentrations and are considered an emerging therapy for Gaucher Disease (GD). Amphiphilic PCs show more favourable cross‐membrane properties and have a higher activity on cells than hydrophilic PCs. To investigate whether the biological activity of amphiphilic iminosugars is related to their state as monomers or as micellar aggregates, we synthesized some novel N ‐alkylated iminosugars and performed physico‐chemical characterizations in the solid state and in aqueous dispersion of the best compound in terms of biological activity. The results suggest that the C12 N ‐alkylated iminosugar 10 exerts its biological activity in the monomeric state, and that the low cell viability observed in the presence of a 50 μM concentration of compound 10 is not related to the formation of micellar aggregates in solution. Abstract : Pharmacological chaperones (PCs) are new therapeutics for protein misfolding diseases, and amphiphilic PCs perform best in Gaucher Disease patients' cell lines. With the aim of investigating the biological activity vs aggregation behaviour of a new N ‐alkylated iminosugar‐based PC, a complete physicochemical study in solution and in the solid state was performed, which ruled out a self‐assembly based multivalent effect.